Impact of Multimedia Instructional Materials on the Attainment of Higher Order Cognitive Skills: A Literature Review - Bagarukayo, Emily; Mbarika, Victor (International Conference on Information Integration and Web-based Applications & Services, 2008)
In the past decade studies have examined the role of multimedia instructional technologies in improving Higher Order Cognitive Skills (HOCS) (Bradley et al., 2007). Some studies show that it is difficult for learners to deal with decision-making situations that require HOCS. Undergraduate learning has been repeatedly criticized for failing to develop HOCS for Problem solving and Decision making in science education (Mbarika et al., 2003a). This suggests the need for new approaches to address this dilemma. The multimedia instruction is an IT tool developed to understand complex decision making that requires HOCS. There is insufficient research on the impact of multimedia technology on teaching, learning and assessment. This is proven by the paucity of research on the effectiveness and impact of Multimedia materials on HOCS development and on generation of creative instructional delivery. Furthermore, the impact of multimedia instructional materials on “actual” learning has received little research attention. Research (Bradley et al., 2007) shows that studies based on perceived learning prove that Multimedia materials improve the students’ attainment of HOCS. Despite the attention this line of research has gained over past decade, there is no known study that has comprehensively compiled the knowledge base in this domain. In our study we present a comprehensive review of published studies that have examined the role of multimedia in improving HOCS of the learner. In all we find that these studies reveal four themes: (i) studies use only quantitative methods; (ii) studies are based on perceived learning; (iii) studies need to address actual learning; (iv) studies don’t consider students’ learning styles; (v) studies were carried out in one university. Our study aids researchers in this domain and those interested in doing work in this domain to have a sense of the direction needed to proceed.
Keywords: Higher Order Cognitive Skills; Multimedia; Learning; Teaching